Selected health problems of a child with juvenile idiopathic arthritis – nursing care based on scientific evidence - Wołek, Agnieszka; Cepuch, Grażyna; Kruszecka-Krówka, Agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2024)
Juvenile idiopathic arthritis (JIA) is one of the most common arthropathies. It belongs to a heterogeneous group of diseases, the main mechanism of which is a long-term, chronic inflammatory process. Selected health problems in a child include chronic pain and morning stiffness, fever, difficulty in basic physical activity, and the risk of nutritional deficiencies. Problems resulting from the chronicity of the disease determine the effectiveness of treatment, independence, and the survival of the patient. The purpose of this publication is to introduce the condition and present selected health problems of a patient with JIA as well as to propose methods of solving them through the actions of the nursing team. The individualised approach of the team working should consider not only the advancement of the disease process and its treatment, but also the patient’s developmental stage with age-related needs and anatomophysiological differences.